MARKETING STRATEGY ANALYSIS TO IMPROVE BRAND IMAGE ON THE INSTAGRAM ACCOUNT @MIXUEINDONESIA - Muchammad Riza Zulfikar; Didik Hariyanto (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the marketing tactics employed by the Instagram account @MixueIndonesia in enhancing brand image and customer engagement. Method: A qualitative content analysis was conducted using five screenshots of posts from January to March 2023. Primary data were collected through systematic observation and documentation of the account’s content, while secondary data were obtained from relevant literature and supporting articles. Results: The findings indicate that @MixueIndonesia effectively strengthens its brand image by utilizing engaging visual content, interactive captions, and personalized greetings such as “Mixue Lovers.” Additionally, the use of distinctive product packaging featuring the Mixue logo, the slogan “Share Sweetness, Spread Happiness,” and consistent visual identity further enhance consumer recognition and emotional connection with the brand. Novelty: This research contributes to the understanding of how consistent visual branding and interactive social media strategies can effectively build brand image and loyalty within the food and beverage industry, particularly through Instagram-based marketing approaches.